Perspectives on ICT from Inside Al-Ula Schools - Albalawi, Fahad (Technium Social Sciences Journal, 2021)
As the following chapter demonstrates, data collected from both the online survey and a telephone interview offered valuable insights into the perspectives of teachers and principals on the use of information and communication technology (ICT) within Al-Ula schools. Interview data collected from ten teachers and four principals was coded and analyzed in order to discover themes that existed across the data set. In the following chapter, these themes will be discussed in greater detail. This chapter also contains an analysis of data drawn from surveys on technology use that were distributed to teachers. As noted in Chapter 3, the primary function of the online survey was to provide descriptive statistics that helped to contextualize the interview data. As sixty-one teachers participated in the survey, the survey data gives us a broader view of the how technology is being used in Al-Ula schools, and what some of the obstacles might be to further implementing technology within the schools. Nine principals also completed the survey, and their responses will also be referred to throughout this chapter.